2020
DOI: 10.1111/ctr.13824
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous urinary glucocorticoid metabolites and mortality in prednisolone‐treated renal transplant recipients

Abstract: Background: Chronic corticosteroid treatment suppresses HPA-axis activity and might alter activity of 11β hydroxysteroid dehydrogenases (11β-HSD). We aimed to investigate whether the endogenous glucocorticoid production and 11β-HSD activities are altered in prednisolone-treated renal transplant recipients (RTR) compared with healthy controls and whether this has implications for long-term survival in RTR. Methods: In a longitudinal cohort of 693 stable RTR and 275 healthy controls, 24-hour urinary cortisol, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Inter-individual variability in the sensitivity of the HPAA to exogenous glucocorticoids has been observed 44128129. For example, higher cortisol after administration of dexamethasone was associated with an inadequate response to the low dose ACTH stimulation test after a 14 day course of prednisolone in healthy volunteers 44.…”
Section: Factors Affecting Likelihood Of Glucocorticoid Induced Adrenal Insufficiencymentioning
confidence: 99%
“…Inter-individual variability in the sensitivity of the HPAA to exogenous glucocorticoids has been observed 44128129. For example, higher cortisol after administration of dexamethasone was associated with an inadequate response to the low dose ACTH stimulation test after a 14 day course of prednisolone in healthy volunteers 44.…”
Section: Factors Affecting Likelihood Of Glucocorticoid Induced Adrenal Insufficiencymentioning
confidence: 99%
“…Age- and sex-related values provided for ratio 47 and ratio 49, both reflecting 5α-reductase deficiency, published by C. W. Weykamp et al in 1989 were all within current reference intervals [ 14 ]. The same applied for values obtained from different publications: (1) by Farese et al in 1991 concerning ratios 49, 56 and 57, the latter two reflecting 11β-HSD type 1 deficiency, (2) by Soro et al in 1995 concerning ratio 49 and ratio 53 (11β-HSD type 1 deficiency), (3) by Finken et al in 1999 concerning ratio 49 and ratio 52 (11β-HSD type 1 deficiency), and (4) by Vulto et al in 2020 concerning ratio 52 and ratio 53 [ 15 17 , 20 ]. Values published by Finken et al in 1999 for ratio 53 were remarkably higher than the current reference intervals for both sexes and also higher than all other corresponding values cited in S1 Table .…”
Section: Resultsmentioning
confidence: 99%
“…Ratios Ratio ID References 11βOHET/11βOHAT [9][10][11][12] THF/5αTHF [9][10][11][12][13][14][15][16][17][18] THB/5αTHB [9][10][11][12][13] CYP19A1/Aromatase deficiency (CYP19A1D) testosterone/17β-estradiol [9] 11β-hydroxysteroid dehydrogenase type 2 deficiency (11βHSD2D) c F/E [9,11,12,15,19,20] (THF+5αTHF)/THE [9][10][11][12][13]15,[17][18][19][20][21] (αC+βC)/(αCl+βCl) [9] (F+E)/(THF+5αTHF+THE) [9] 11β-hydroxysteroid dehydrogenase type 1 deficiency (11βHSD1D) d THE/(THF+5αTHF) [9][10][11][12]14,16] (αCl+βCl)/(αC+βC) [9,11,12,16] 20α-hydroxysteroid dehydrogenase (20αHSD) (THF...…”
Section: Enzymes Pathways and Disordersmentioning
confidence: 99%
“…This study is designed as a cross-over trial as previous studies have demonstrated a high interindividual variation for the effect of exogenous corticosteroids 16 17. One intervention consists of two doses of prednisolone (11β,17,21-trihydroxy-1,4-pregnadieen-3,20-dion).…”
Section: Methods and Analysismentioning
confidence: 99%